NORMA PEDAGOGIS DAN ANALISIS KEBUTUHAN BELAJAR DALAM PEMBELAJARAN BAHASA INDONESIA UNTUK PENUTUR ASING (BIPA) - Suyitno, Imam (Diksi, 2008)
The teaching-learning process of Indonesian involving foreigners as thelearners differs in characteristics from the teaching-learning process of Indonesianin general. The differences are due to the learners' cultural backgrounds. Ananalysis of their learning needs and pedagogical norms of language learning isrequired in the selection of the materials and strategies for the teaching-learningprocess of Indonesian involving them as the learners. Results of analysis on theirentry level, learning style, and learning objective will direct the teachers inselecting the language teaching materials and strategies. In addition, the materialsand strategies are also influenced by the teachers' own pedagogical norms.Keywords: needs analysis, pedagogical norms, teaching materials, teachingstrategies